2024
DOI: 10.1101/2024.01.26.577428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large-scale characterization of drug mechanism of action using proteome-wide thermal shift assays

Jonathan G. Van Vranken,
Jiaming Li,
Julian Mintseris
et al.

Abstract: In response to an ever-increasing demand of new small molecules therapeutics, numerous chemical and genetic tools have been developed to interrogate compound mechanism of action. Owing to its ability to characterize compound-dependent changes in thermal stability, the proteome-wide thermal shift assay has emerged as a powerful tool in this arsenal. The most recent iterations have drastically improved the overall efficiency of these assays, providing an opportunity to screen compounds at a previously unpreceden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…In summary, our data show that live-cell PISA can be useful to study pathway interactions but falls short for the unambiguous assignment of direct rocaglate targets. We therefore opted to measure thermal stabilization in cell lysate to allow for improved detection of direct ligand-protein engagement while muting network effects (47).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, our data show that live-cell PISA can be useful to study pathway interactions but falls short for the unambiguous assignment of direct rocaglate targets. We therefore opted to measure thermal stabilization in cell lysate to allow for improved detection of direct ligand-protein engagement while muting network effects (47).…”
Section: Resultsmentioning
confidence: 99%
“…apparent stabilization) through multiple indirect mechanisms ( e.g. protein expression, cellular localization) (47). This is particularly salient for rocaglates, which acutely alter protein abundance through cap-dependent translation inhibition, making it unclear whether fold-change differences arise from ligand-induced stabilization or modulation of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we compared total proteomics and thermal stability analyses after belinostat treatment to integrate understanding of early HDACi action (thermal stability) and downstream effects (total proteomics) (Supplementary Figure 8A, B, D). Owing to the potential importance of cellular and chromatin context in affecting HDACi engagement, we have previously found that both cell- and lysate-based analyses were complementary for deciphering the molecular effects of chemical perturbations in cancer cells (Van Vranken et al, 2024). From the thermal stability analysis, we observed clear engagement of belinostat and vorinostat with HDAC1, HDAC2, HDAC6 (Figure 8B).…”
Section: Resultsmentioning
confidence: 99%